Clinical Characteristics and Genetic Variations in Early-Onset Atopic Dermatitis Patients - Kim, Beom Jun; Wang, Hye-young; Lee, Hyeyoung; Lee, So-Yeon; Hong, Soo-Jong; Choi, Eung Ho (Annals of dermatology, 2019)
Hereditary factors contribute to atopic dermatitis (AD) development. We developed the reverse blot hybridization assay (REBA) kit to simultaneously detect variations in skin barrier- and immune response-related genes prevalent in Korean AD patients. To identify genetic variations and clinical characteristics that could predict early AD development. We compared AD-related genetic variations between early-onset AD subjects and non-AD controls, and clinical characteristics and genetic variations between early- and late-onset AD subjects. We compared 28 early-onset AD subjects and 57 non-AD controls from a birth cohort and 108 early- (age ≤3 years) and 90 late-onset AD subjects and 189 non-AD controls from a university hospital. Genetic variations were detected via REBA. There were no differences in AD-related genetic variation between early-onset AD subjects and non-AD controls in the birth cohort. When the birth cohort and hospital populations were combined, early-onset AD subjects and non-AD controls showed different frequencies of genetic variations of , , , , , and . No differences in the frequency of genetic variations were observed between early- and late-onset AD subjects. Immunoglobulin E positivity for house dust mites was prevalent in late-onset AD subjects. A family history of atopic diseases was associated with early-onset AD. No AD-related genetic variations could predict early AD development in Koreans, even though neonates with a family history of atopic diseases are likely to develop AD at ≤3 years of age. Environmental exposure may be more important than genetic variation in determining the onset age of AD.